2019
DOI: 10.1371/journal.pone.0214355
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease complications: Prevalence and resource utilization

Abstract: Objectives This study evaluated the prevalence rate of vaso-occlusive crisis (VOC) episodes, rates of uncomplicated and complicated VOC episodes, and the primary reasons for emergency room (ER) visits and inpatient admissions for sickle cell disease (SCD) patients. Methods The Medicaid Analytic extracts database was used to identify adult SCD patients using claims from 01JUL2009-31DEC2012. The date of the first observed SCD claim was designated as the index date. Patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 23 publications
1
50
3
Order By: Relevance
“…Some researchers use the presence of ≥1 claim in any setting with an SCD diagnosis code to identify putative SCD cases. [61][62][63][69][70][71][72][73] However, owing to the frequency of false-positive diagnoses in outpatient claims, that approach can lead to misclassification and result in underestimation of the use of services or costs among individuals with SCD. 20…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers use the presence of ≥1 claim in any setting with an SCD diagnosis code to identify putative SCD cases. [61][62][63][69][70][71][72][73] However, owing to the frequency of false-positive diagnoses in outpatient claims, that approach can lead to misclassification and result in underestimation of the use of services or costs among individuals with SCD. 20…”
Section: Discussionmentioning
confidence: 99%
“…The [58][59][60][61][62][63][64][65][66]. Prospective cohort studies of SCD patients are rare in Africa due to barriers to medical monitoring [37].…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in high-income countries have sufficiently demonstrated the benefits of standardized and regular medical follow-up of sickle cell patients, with a reduction in acute and chronic complications of the disease and improvement in the quality of life [58][59][60][61][62][63][64][65][66]. Prospective cohort studies of SCD patients are rare in Africa due to barriers to medical monitoring [37].…”
Section: Discussionmentioning
confidence: 99%